Validation of the Erlangen Score Algorithm for the Prediction of the Development of Dementia due to Alzheimer's Disease in Pre-Dementia Subjects - Lewczuk, Piotr; Kornhuber, Johannes; Toledo, Jon B; Trojanowski, John Q; Knapik-Czajka, Malgorzata; Peters, Oliver; Wiltfang, Jens; Shaw, Leslie M (Journal of Alzheimer's disease, 2015)
In previous studies, a dichotomous stratification of subjects into "cerebrospinal fluid (CSF) normal" and "CSF pathologic" was used to investigate the role of biomarkers in the prediction of progression to dementia in pre-dementia/mild cognitive impairment subjects. With the previously published Erlangen Score Algorithm, we suggested a division of CSF patterns into five groups, covering all possible CSF result combinations based on the presence of pathologic tau and/or amyloid-β CSF values. This study aimed to validate the Erlangen Score diagnostic algorithm based on the results of biomarkers analyses obtained in different patients cohorts, with different pre-analytical protocols, and with different laboratory analytical platforms. We evaluated the algorithm in two cohorts of pre-dementia subjects: the US-Alzheimer's Disease Neuroimaging Initiative and the German Dementia Competence Network. In both cohorts, the Erlangen scores were strongly associated with progression to Alzheimer's disease. Neither the scores of the progressors nor the scores of the non-progressors differed significantly between the two projects, in spite of significant differences in the cohorts, laboratory methods, and the samples treatment. Our findings confirm the utility of the Erlangen Score algorithm as a useful tool in the early neurochemical diagnosis of Alzheimer's disease.